Microbial risk assessment and antimicrobial resistance - Ahmed, S. (Elsevier, 2019)
The exposure of microorganisms that are antimicrobial resistant in humans as well as in animal feed poses a serious concern globally. A serious discussion needs to occur between the usage of antimicrobials in manufacturing of the animal feed and exposure of the resistant organisms in the human beings. A microbial risk assessment is used to ease the risk of scientific analysis that is linked to the food web involving estimation of unpredictability and sequence of the control procedures. It is considered as an important scientific tool and can be used to estimate the extent of the disclosure and upcoming risk to the human health related to the distinct types of resistance of particular organisms. There are various disclosure ways to antimicrobial resistance emerging from waste of humans and each should be estimated for its comparative risk to health of human. This chapter skims the antimicrobial risk assessment in food safety, environment, water, and sanitation covering the management and regulation of risk assessment. It also assesses the current applications of microbial risk assessment related to the resistance against microbes concentrating on procedures, presumption, and the data restrictions. As the results of microbial risk assessment are based on the data input quality, so this chapter also focuses on production related to high standard of data narrating the characteristics that data must ideally possess for microbial risk assessment. Â© 2020 Elsevier Inc. All rights reserved.